ON THE EVOLUTION OF DIPODIUM R. BR. - Peter O'byrne (Research Center for Biology, 2014)
Dipodium R. Br. (Orchidaceae), a genus of ca. 38 species, should be divided into an Australasian clade and a Malesian clade, based on morphological and geographic evidences. Dipodium section Dipodium and section Leopardanthus (Blume) O. Kuntze are re-defined to accommodate this change. An evolutionary scenario that explains this division is proposed. The lack of diversity of floral structure in the genus is probably caused by pollinator-specificity, while the diversity of plant form may be due to long-term environmental factors. An evolutionary explanation is suggested for the complex between Dipodium fevrellii J. J. Sm. and the hybrid D. pandanum Bailey in New Guinea. The complex in Java involving D. pictum (Lindl.) Rchb. f. and D. scandens (Bl.) J. J.Sm. is discussed, and the presence of a hybrid noted.In Borneo, the complex taxonomic situation caused by repeated inter-breeding of populations is noted.